Sinal sobre o abismo: da totalidade do epos à fragmentação enquanto busca pelo sentido - Costa, Flávio Eduardo Cristino da (2017)
This dissertation aims to present a perspective of the so well studied totality in the literary and aesthetic debate, with emphasis on the Theory of the novel and on the Soul and form, from the young Lukács, and on the Benjaminian esssays. The effort of this project, however, does not manifest itself exclusively through a specific philosophical glossary, but it is also in the exposition of the elements that compose the totality, in the constellation of themes and images that permeate this subject of the epic, and specially with regard to the their consequent fragmentation. That is to say, in this context it is essential to have in mind the established relation between the epics of Greek antiquity (the epos of the totality) and the development of its dimensions throughout the historical process. The two main leitmotif of this text are nostalgia and the sea: the first consists in the longing for the meaning of totality, the nostalgia of the sense of wholeness of which modernity is abandoned, the second is a metaphor for the flow of narratives and metaphor for the relationship between the divine/unknown over the human